Evolving a Collaborative Scientific Text. - Marchese, Francis T. (International Journal of the Book, 2009)
Journals and ultimately monographs are the de facto media for communicating results of scientific research. Yet, they exhibit a number of limitations. At their core resides the scientific text, a concise narrative that is responsible for the bulk of communication. Imagery is relegated the subservient role of illustrating the essential points set forth. In contrast, the interactive visualization software that created this imagery may have been run special output devices that provide a level of visual description and detail not expressible in traditional print media. Conversely, scientific visualization systems are ill equipped to accommodate, annotate, and format the large body of text required for a complete document. Finally, journals and monographs tend to be closed, difficult to annotate, and append. With these issues in mind, this presentation will demonstrate how the use of collaborative technologies such as wikis can be used to merge scientific texts with visualization systems. This approach binds together two segments of the scientific visualization process - the visualization of complex experimental data with the publication of results and analysis. Such a system can support interactive, visually complex documents that may be augmented with new insights, can evolve over time, and is a focal point for collaborative extension of the scientific narrative.